Synaptic behavior of Fe₃O₄-based artificial synapse by electrolyte gating for neuromorphic computing - Monalisha, P. (2023)
Neuromorphic computing (NC) is a crucial step toward realizing power-efficient artificial intelligence systems. Hardware implementation of NC is expected to overcome the challenges associated with the conventional von Neumann computer architecture. Synaptic devices that can emulate the rich functionalities of biological synapses are emerging. Out of several approaches, electrolyte-gated synaptic transistors have attracted enormous scientific interest owing to their similar working mechanism. Here, we report a three-terminal electrolyte-gated synaptic transistor based on Fe3O4 thin films, a half-metallic spinel ferrite. We have realized gate-controllable multilevel, non-volatile, and rewritable states for analog computing. Furthermore, we have emulated essential synaptic functions by applying electrical stimulus to the gate terminal of the synaptic device. This work provides a new candidate and a platform for spinel ferrite-based devices for future NC applications.